Strengthening global health security by embedding the International Health Regulations requirements into national health systems. (20th January 2018) - Kluge, Hans; Martín-Moreno, Jose Maria; Emiroglu, Nedret; Rodier, Guenael; Kelley, Edward; Vujnovic, Melitta; Permanand, Govin
Abstract : The International Health Regulations (IHR) 2005, as the overarching instrument for global health security, are designed to prevent and cope with major international public health threats. But poor implementation in countries hampers their effectiveness. In the wake of a number of major international health crises, such as the 2014 Ebola and 2016 Zika outbreaks, and the findings of a number of high-level assessments of the global response to these crises, it has become clear that there is a need for more joined-up thinking between health system strengthening activities and health security efforts for prevention, alert and response. WHO is working directly with its Member States to promote this approach, more specifically around how to better embed the IHR (2005) core capacities into the main health system functions. This paper looks at how and where the intersections between the IHR and the health system can be best leveraged towards developing greater health system resilience. This merging of approaches is a key component in pursuit of Universal Health Coverage and strengthened global health security as two mutually reinforcing agendas.